2014
DOI: 10.1007/978-1-4939-0320-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes and Adaptive Angioplasticity: The Role of Tumor Necrosis Factor-Like Weak Inducer of Apoptosis (TWEAK)

Abstract: The TNF superfamily member TWEAK has emerged as a pleiotropic cytokine that regulates many cellular functions that include immune/inflammatory activity, angiogenesis, cell proliferation, and fate. TWEAK through its inducible receptor, FGF-inducible molecule 14 (Fn14), can induce both beneficial and deleterious activity that has a profound effect on cell survival. Thus it is highly likely that TWEAK and Fn14 expressed by cells of the neurovascular unit help regulate and maintain vascular and tissue homeostasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…Binding of TWEAK to Fn14 recruits cellular inhibitor of apoptosis (cIAP1), TRAF2, TRAF5, and/or TRAF6 into a complex to activate transforming growth factor B-activated kinase 1 (TAK1), NF-κB -inducing kinase (NIK), and mitogen activated protein kinase kinases (MKK) [28]. Activation of TGF-B-activated kinase-1 TAK1 stimulates IB kinase (IKKB) leading to the activation of the early canonical NF-κB pathway characterised by nuclear translocation of RelA [28,29]. NIK phosphorylates and activates IKKB leading to prolonged, but slower, activation of the non-canonical NF-κB pathway symbolised by increased DNA-binding activity of the p52/RelB NF-κB complex [23].…”
Section: Canonical and Non-canonical Nf-κb Pathwaysmentioning
confidence: 99%
“…Binding of TWEAK to Fn14 recruits cellular inhibitor of apoptosis (cIAP1), TRAF2, TRAF5, and/or TRAF6 into a complex to activate transforming growth factor B-activated kinase 1 (TAK1), NF-κB -inducing kinase (NIK), and mitogen activated protein kinase kinases (MKK) [28]. Activation of TGF-B-activated kinase-1 TAK1 stimulates IB kinase (IKKB) leading to the activation of the early canonical NF-κB pathway characterised by nuclear translocation of RelA [28,29]. NIK phosphorylates and activates IKKB leading to prolonged, but slower, activation of the non-canonical NF-κB pathway symbolised by increased DNA-binding activity of the p52/RelB NF-κB complex [23].…”
Section: Canonical and Non-canonical Nf-κb Pathwaysmentioning
confidence: 99%
“…Additionally, CD163 has been reported to mediate the uptake of TWEAK, leading to the repression of Fn14 activation and the subsequent proinflammatory response [ 17 ]. The binding of TWEAK to Fn14 activates classical and non-classical cascades within the NF-κB pathway [ 54 , 55 ]. Furthermore, the addition of soluble CD163 protein was found to increase the formation of the CD163-TWEAK complex, which may be internalized by macrophages to induce the degradation of TWEAK.…”
Section: Discussionmentioning
confidence: 99%
“…Pericytes are multifunctional cells found on pre-capillary arterioles, capillaries, and post-capillary venules (Bonkowski et al, 2011; Dalkara et al, 2011; Dore-Duffy, 2014; Hill et al, 2014; Winkler et al, 2011). They are embedded within the endothelial basement membrane (Attwell et al, 2010; Dalkara et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that astrocytes and pericytes are both involved in the formation and maintenance of capillary like structures by endothelial cells (Itoh et al, 2011). Studies have also shown that astrocytes are necessary for barriergenesis and directly regulate factors modulating BBB formation, such as tight junction proteins, SSeCKS, Ang-1 and TGFβ (Bonkowski et al, 2011; Dore-Duffy and LaManna, 2007; Dore-Duffy, 2014; Garcia et al, 2004; Lee et al, 2003; Rieckmann and Engelhardt, 2003; Rubin et al, 1991). …”
Section: Introductionmentioning
confidence: 99%